Is human achilles tendon deformation greater in regions where cross-sectional area is smaller? - Reeves, N. D.; Cooper, G. (The Journal of Experimental Biology, 2017)
The Achilles is a long tendon varying in cross-sectional area (CSA) considerably along its length. For the same force, a smaller CSA would experience higher tendon stress and we hypothesised that these areas would therefore undergo larger transverse deformations. A novel magnetic resonance imaging-based approach was implemented to quantify changes in tendon CSA from rest along the length of the Achilles tendon under load conditions corresponding to 10%, 20% and 30% of isometric plantar flexor maximum voluntary contraction (MVC). Reductions in tendon CSA occurring during contraction from the resting condition were assumed to be proportional to the longitudinal elongations within those regions (Poisson's ratio). Rather than tendon regions of smallest CSA undergoing the greatest deformations, the outcome was region specific, with the proximal (gastrocnemius) tendon portion showing larger transverse deformations upon loading compared with the distal portion of the Achilles (P<0.01). Transverse tendon deformation only occurred in selected regions of the distal Achilles tendon at 20% and 30% of MVC, but in contrast occurred throughout the proximal portion of the Achilles at all contraction levels (10%, 20% and 30% of MVC; P<0.01). Calculations showed that force on the proximal tendon portion was ~60% lower, stress ~70% lower, stiffness ~30% lower and Poisson's ratio 6-fold higher compared with those for the distal portion of the Achilles tendon. These marked regional differences in mechanical properties may allow the proximal portion to function as a mechanical buffer to protect the stiffer, more highly stressed, distal portion of the Achilles tendon from injury.